Oceanographic conditions over the continental shelf off Magdalena Bay (Mexico) in 2011–2012 - Zaitsev, Oleg; Trasviña-Castro, Armando; Linero-Cueto, Jean; Gaxiola-Castro, Gilberto; Cepeda-Morales, Jushiro (Ciencias Marinas, 2014)
The hydrophysical results obtained during six oceanographic cruises in 2011 (February, April, July, and October) and 2012 (February and April) over a 50-station sampling grid in front of the Magdalena-Almejas lagoon system (Mexico) are presented. MODIS-Aqua sensor data (1.1 km) of sea surface temperature (SST) and chlorophyll a, and geostrophic current fields were analyzed during the sampling periods. In the northern part of the study area the pattern of the thermohaline structure shows subsurface intrusion of modified subarctic water, especially during February and April of both years. To the south, in July and October 2011, evident indications of subtropical subsurface water were found. The geostrophic current fields in February and April show a surface southward flow along the coast, which changes direction towards the North Pole in July and October. In spring, the satellite-derived SST showed negative anomalies of up to 4.5 ºC in the coastal zone, corresponding to cold upwelled water rising to the surface from a depth of 60–70 m. Based on the results, the study area can be considered the southern boundary of the transition zone between the subarctic and subtropical waters of the northeastern Pacific Ocean, with marked seasonality.